Field notes contributed by Tanya Bray, fall 1987 - Bray, Tanyaet al (1987)
Fall report of birds and locations contributed by Tanya Bray and other observers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1987. Epson - sheet feed